Regional Inequality and Classification of Leading Sectors Economy Province Nusa Tenggara Timur - Maulia Putri Bestari; Endang Endang (MediaTrend, 2025)
This paper aims to examine economic inequality and identify leading sectors in 10 districts/ cities in NTT Province in order to formulate policies that can encourage inclusive and sustainable economic growth. This study uses annual panel data from 10 districts/cities in Nusa Tenggara Timur Province in the period 2019-2023, with data analysis techniques using the Williamson Index, Location Quotient (LQ), and Klassen Typology to measure development inequality, basic sectors, and economic growth patterns between regions. This study uses the Stata 16 and MS. Excel 2011 analysis tools. The results of this study indicate that although several regions in NTT, such as Kupang City, show rapid economic growth and are in the developed region quadrant, most other districts/cities are still lagging behind in terms of development and economy, with non-basic sectors that have not yet developed significantly, as well as uneven distribution of wealth and infrastructure access.